2015
DOI: 10.1590/1807-3107bor-2015.vol29.0057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reverse headgear on pharyngeal airway in patients with different vertical craniofacial features

Abstract: The aim of this study was to investigate the effects of reverse headgear (RH) on pharyngeal airway morphology in two groups of Class III patients with different vertical craniofacial features in comparison with an untreated Class III group. Seventeen subjects (9 males, 8 females; mean age 11.3 ± 0.98 years) with optimum vertical growth and 17 subjects (10 males, 7 females, mean age 11.5 ± 1.1 years) with a vertical growth pattern treated with a removable intra-oral appliance and a Delaire type facemask were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…To the best of our knowledge, no meta‐analysis has evaluated the pharyngeal airway space changes, either 2D or 3D, after RME and/or FM protraction treatment(s). Studies with 2D evaluation found that RME/FM is significantly related to the upper pharyngeal airway . In the present study, our results indicated that the patients who received RME/FM therapy were more likely to have an increased upper pharyngeal airway than those untreated in the control group (Figure ).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…To the best of our knowledge, no meta‐analysis has evaluated the pharyngeal airway space changes, either 2D or 3D, after RME and/or FM protraction treatment(s). Studies with 2D evaluation found that RME/FM is significantly related to the upper pharyngeal airway . In the present study, our results indicated that the patients who received RME/FM therapy were more likely to have an increased upper pharyngeal airway than those untreated in the control group (Figure ).…”
Section: Discussionsupporting
confidence: 57%
“…In this meta‐analysis, nine studies were included for analysis . Using Review Manager Version 5.3 software (Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, 2014), the mean difference and 95% confidence intervals (CI) were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A skeletal change that can occur from orthopedic treatment of Class III malocclusion is the alteration of the size of airway [7,8]. Several studies [6,[9][10][11] evaluated the effects of FM appliances with or without rapid maxillary expansion (RME) on the oropharyngeal and nasopharyngeal dimensions with controversial results. The major limitation of all these studies is the short-term nature of the observations.…”
Section: Introductionmentioning
confidence: 99%